On some models of temperature of asperities at friction - Diamandiev, Vassil (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
In this paper we generalize the model of temperature of asperities given by Chichinadze Ginzburg [2]. In the paper [2] the problem of temperature is considered at the assumption of two hypotheses: 1) The dimensions of the bodies which are perpendicular to the friction surface are infinite; 2) The thermal flux of the friction is constant. In the present paper both restriction are generalized and the thermal flux is taken to be a linear function of time. a model of a single asperity for which the termal balance is given and its temperature is directly determined is developed.